2018
DOI: 10.1177/105268461802800205
|View full text |Cite
|
Sign up to set email alerts
|

Home as the Least Restrictive Environment for Students with Medical Disabilities

Abstract: School leaders have a prominent role on Individual Education Program (IEP) teams and often face very challenging obstacles when determining substantive educational services and placement in the least restrictive environment (LRE) for students with medical disabilities. In absence of federal statutory and regulatory policy, standard legal research methodology was used to determine whether explicit and implicit recommendations existed for school leaders elsewhere in the law for the use of homebound placements fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Engaging in Varying Taskwork-Oriented Actions Depending on Goals and Tasks. A total of 20 reviewed studies suggested varying taskwork-oriented actions in which effective SLTs differently engaged according to their goals and tasks (Baecher et al, 2013;Carpenter, 2015;Chang, 2019;Dematthews, 2015;Eckert, 2019;Frick et al, 2013;Green, 2017;Halverson et al, 2015;Halverson & Clifford, 2013;Ishimaru, 2018;Judkins et al, 2019;Klar & Brewer, 2013;Leis et al, 2017;Levin & Schrum, 2014;Liou, 2015;Lustig, 2018;Mansfield et al, 2018;Mayer et al, 2013;Scanlan, 2013;Scanlan et al, 2016). The goals and tasks stemmed from school vision, mission, goals, and/ or strategies, including: (a) policy/program implementation, (b) social equity, (c) school improvement/change with a focus on instruction improvement, (d) English Learner (EL) education, (e) special education, (f) data-driven practice, (g) collective leadership development, and/or (h) risk management.…”
Section: Substantive Features Of the Reviewed Researchmentioning
confidence: 99%
See 3 more Smart Citations
“…Engaging in Varying Taskwork-Oriented Actions Depending on Goals and Tasks. A total of 20 reviewed studies suggested varying taskwork-oriented actions in which effective SLTs differently engaged according to their goals and tasks (Baecher et al, 2013;Carpenter, 2015;Chang, 2019;Dematthews, 2015;Eckert, 2019;Frick et al, 2013;Green, 2017;Halverson et al, 2015;Halverson & Clifford, 2013;Ishimaru, 2018;Judkins et al, 2019;Klar & Brewer, 2013;Leis et al, 2017;Levin & Schrum, 2014;Liou, 2015;Lustig, 2018;Mansfield et al, 2018;Mayer et al, 2013;Scanlan, 2013;Scanlan et al, 2016). The goals and tasks stemmed from school vision, mission, goals, and/ or strategies, including: (a) policy/program implementation, (b) social equity, (c) school improvement/change with a focus on instruction improvement, (d) English Learner (EL) education, (e) special education, (f) data-driven practice, (g) collective leadership development, and/or (h) risk management.…”
Section: Substantive Features Of the Reviewed Researchmentioning
confidence: 99%
“…The goals and tasks stemmed from school vision, mission, goals, and/ or strategies, including: (a) policy/program implementation, (b) social equity, (c) school improvement/change with a focus on instruction improvement, (d) English Learner (EL) education, (e) special education, (f) data-driven practice, (g) collective leadership development, and/or (h) risk management. For instance, Lustig (2018) suggested what Individualized Education Program (IEP) teams should do to provide better special education for students with medical disabilities. The team actions in Lustig's (2018) study included: (a) offering "students a full individual evaluation to determine individual needs prior to homebound instructional placement" (p. 279), or (b) "obtaining physician's recommendation to document need for homebound instructional placement" (p. 281).…”
Section: Substantive Features Of the Reviewed Researchmentioning
confidence: 99%
See 2 more Smart Citations